Etika Jurnalistik dalam Praktik Pemberitaan Media Cetak: Analisis Observasi Redaksi dan Teks Berita Harian Waspada - Darni Angkat; Ghina Septika (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study addresses the issue of how journalistic ethics are implemented in print media reporting amid the dynamics of news production and demands for immediacy. The study aims to analyze the application of journalistic ethical principles in the editorial process and news texts of Harian Waspada, focusing on accuracy, balance of sources, independence, non-sensationalism, and social responsibility. A qualitative descriptive approach was employed, with data collected through direct observation during an internship program in the editorial newsroom and qualitative analysis of selected news articles published by Harian Waspada. Data analysis was conducted using the interactive model of Miles and Huberman, combined with qualitative content analysis. The findings indicate that Harian Waspada demonstrates a relatively consistent commitment to accuracy and social responsibility, while efforts to maintain source balance and editorial independence are generally evident. However, limitations in achieving ideal balance were identified in certain types of news, particularly brief reports and official statements, due to efficiency considerations and news characteristics. Overall, the study concludes that journalistic ethics at Harian Waspada are practiced in a contextual and adaptive manner within editorial routines, reflecting the media’s commitment to public interest and professional journalism standards.